Outcomes and Acceptability of Telehealth-Based Coaching for Caregivers in Asian Countries. Issue 2 (March 2023) - Tsami, Loukia; Nguyen, Jennifer Trang; Alphonso, Naomi; Lerman, Dorothea; Matteucci, Marissa; Chen, Ning
Recent studies evaluating the effectiveness of using telehealth to train caregivers across large geographical distances in the United States and internationally indicate that this modality can increase families' accessibility to evidence-based interventions for problem behavior. In this study, experimenters and interpreters in the United States remotely coached nine caregivers of children with disabilities residing in three countries in Asia to implement functional analyses (FA) and functional communication training (FCT). Five of the nine families were culturally matched to either the experimenter or the interpreter. Problem behavior was reduced to near-zero levels for all but one participant. Furthermore, all caregivers implemented the procedures with high levels of integrity and rated the assessment and treatment as highly acceptable, regardless of cultural matching or use of interpreters. Overall, findings suggest telehealth-based caregiver coaching and caregiver-implemented FA plus FCT is feasible and acceptable in Asia.